Photophysical characterization of light-emitting poly(indenofluorene)s - Keivanidis, Panagiotis E.; Jacob, Josemon; Oldridge, Luke; Sonar, Prashant; Carbonnier, Benjamin; Baluschev, Stanislav; Grimsdale, Andrew C.; Müllen, Klaus; Wegner, Gerhard (My University, 2005)
Time-resolved photoluminescence spectroscopy experiments of three poly(2,8-indenofluorene) derivatives bearing different pendant groups are presented. A comparison of the photophysical properties of dilute solutions and thin films provides information on the chemical purity of the materials. The photophysical properties of poly(2,8-indenofluorene)s are correlated with the morphological characteristics of their corresponding films. Wide-angle X-ray scattering experiments reveal the order in these materials at the molecular level. The spectroscopic results confirm the positive impact of a new synthetic approach on the spectral purity of the poly(indenofluorene)s. It is concluded that complete side-chain substitution of the bridgehead carbon atoms C-6 and C-12 in the indenofluorene unit, prior to indenofluorene ring formation, reduces the probability of keto formation. Due to the intrinsic chemical purity of the arylated derivative, identification of a long-delayed spectral feature, other than the known keto band, is possible in the case of thin films. Controlled doping experiments on the arylated derivative with trace amounts of an indenofluorene-monoketone provide quantitative information on the rates of two major photophysical processes, namely, singlet photoluminescence emission and singlet photoluminescence quenching. These results allow the determination of the minimum keto concentration that can affect the intrinsic photophysical properties of this polymer. The data suggest that photoluminescence quenching operates in the doped films according to the Stern-Volmer formalism.
Keywords: Donor-acceptor systems; Energy transfer; Light-emitting devices; Polymers; Time-resolved spectroscopy